2014
DOI: 10.1186/1471-230x-14-87
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of protease inhibitor based combination therapy in a single-center “real-life” cohort of 110 patients with chronic hepatitis C genotype 1 infection

Abstract: BackgroundThe combination of boceprevir or telaprevir with peginterferon-alfa and ribavirin for the treatment of patients infected with HCV genotype 1 has led to significantly increased rates of sustained virological response (SVR) in phase III trials. There is only limited data regarding the safety and efficacy in a “real-life” cohort.MethodsWe analyzed a cohort of 110 unselected HCV patients who started triple therapy from September 2011 to February 2013 by chart review with focus on the individual course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
15
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
7
15
1
1
Order By: Relevance
“…In previous "real-life" studies SVR rates were remarkably lower than those of the respective phase III trials, e.g. in telaprevir-or boceprevir-based treatment regimens [5]. However, our study largely confirms the results from the NEUTRINO trial with a frequency of SVR12 of 96.4% in treatment naïve patients infected with HCV4 [1] compared to 100% in our cohort for patients receiving SOF/PR.…”
Section: Discussionsupporting
confidence: 85%
“…In previous "real-life" studies SVR rates were remarkably lower than those of the respective phase III trials, e.g. in telaprevir-or boceprevir-based treatment regimens [5]. However, our study largely confirms the results from the NEUTRINO trial with a frequency of SVR12 of 96.4% in treatment naïve patients infected with HCV4 [1] compared to 100% in our cohort for patients receiving SOF/PR.…”
Section: Discussionsupporting
confidence: 85%
“…Percentage of advanced (grade 3) liver fibrosis in our study reached 38,6% and was substantially higher than in registration trials (10-28% of patients). 21 The demographic factors that have an influence on development of DAEs in our study were similar with findings in other studies. 12 The association between coexistence of autoimmune thyroiditis with skin rashes during BOC therapy as well as, correlation between comorbidity of AT with anorectal discomfort were not previously observed.…”
Section: J Dermatol Case Rep 2014 4 Pp 95-102supporting
confidence: 92%
“…[15][16][17] There is more data available regarding the safety profile of the PIs from "real-life" and this data revealed increased risk for severe complications of PI-based treatment in cirrhotic patients. [18][19][20][21] However skin adverse reactions in contrast with other adverse events were comparable with results in clinical trials.…”
Section: Introductionsupporting
confidence: 78%
“…The findings from a number of studies have suggested that the efficacy of DAAs in clinical practice might be less than anticipated. 41 practice and those noted in the clinical trials and should be taken into account. 43 At the time that this analysis took place, there were 2 available medications against HCV in the class of DAAs; however, newer medications have emerged and have been reported to have improved efficacy rates compared with those of the first-generation DAAs 44 and, thus, seem to have gained ground (they have become a popular treatment option).…”
Section: Discussionmentioning
confidence: 99%